Popaschalne świadectwo Parakleta o sądzie Boga nad „światem” w ujęciu J 16,8-11 - Kot, Piotr (Verbum Vitae, 2014)
Holy Spirit plays an important role in the theology of the fourth Evangelist. During the Last Super, and therefore right before his death, Jesus from Nazareth not only foretold the coming of the Holy Spirit, but also designated the nature of his mission. The Paraclete, as Jesus calls him, will “testify about” Jesus (John 15:26) and “will demonstrate to the world what sin, righteousness and judgment are about” (John 16:8). Many scholars, while interpreting these words, point to the juridical function of the Paraclete. Accordingly, the Paraclete would pass right judgment on the world in view of the sin of unbelief. However, a detailed exegetical analysis, taking into account the various narrative techniques employed by the author of the fourth Gospel, among them the technique of misunderstanding, allows for a different interpretation of Jesus’ words. Accusations against Jesus are very frequent in the fourth Gospel. The “world” calls him a “sinner” (8:46) and “one who blasphemes” (10:36). In the context of such charges, the passing of judgment on Jesus, as well as his crucifixion and death, were understood as a revelation of God’s justice in regard to Jesus. The Paraclete’s mission will consist in revealing to the “world” and to the disciples the meaning of these events in a reversed perspective. John describes his task by the use of the technique of irony. The Paraclete will reveal as true that Jesus indeed accepted death as a “sinner”, but in the sense of expiatory sacrifice antitype. For that reason, the justice of God has been realized not “in regard” to Jesus, but “in Jesus.” As a result, the “world’s” judgment on Jesus has, in fact, initiated God’s judgment on the “world” and its ruler. The Paraclete is to give a testimony about the victory of life over death in Jesus Christ, and thus to lead the “world” to faith, and the disciples to the fullness of faith.